Investigation into the Fracture Evolution Law of Overlying Strata Roof in Shallowly Buried “Three-Soft” Coal Seam Fully Mechanized Mining Faces and Its Influence on the Feasibility of Gob-Side Entry Retaining - Guoyou Hu; Yongkang Yang; Shuai Li; Konghao Zhu (Applied Sciences)
To address the feasibility of gob-side entry retaining in the shallow-buried three-soft coal seam fully mechanized mining face (SB-TSCS FMMF) of Xindeng (Zhengzhou, China) Coal Industry, we established a mechanical model of post-mining roof–coal-rock interaction in shallow-buried three-soft coal seams. This study reveals the quantitative relationships between the fracture position of the main roof and parameters such as coal seam thickness and immediate roof elastic modulus, and determines the parameter conditions required for implementing gob-side entry retaining in SB-TSCS FMMF. Critical parameters for the main roof fracture under this geological condition were first identified through particle flow simulation. The results indicate that there exist quantitative relationships between the main roof fracture position and parameters of the coal seam and the immediate roof. The influence degree on the maximum force exerted by the main roof on underlying coal-rock strata decreases in descending order as follows: immediate roof elastic modulus, coal seam thickness, immediate roof thickness, and coal seam elastic modulus. Similarly, the influence degree on the maximum bending moment follows the same order: immediate roof elastic modulus, coal seam thickness, immediate roof thickness, and coal seam elastic modulus. Based on the roof fracture laws, parameter thresholds suitable for gob-side entry retaining in three-soft coal seams are proposed, such as coal seam thickness (≤4 m) and immediate roof thickness (≤8 m). It is found that the main roof fracture position in shallow-buried three-soft coal seams is concentrated within the 0.3–0.6 m stress-sensitive zone at the edge of the goaf, providing key parameter thresholds for the support design of gob-side entry retaining.